LIF measurement in a partially saturated and partially absorbed regime - Dvořák, Pavel; Mrkvičková, Martina; Kratzer, Jan (Frontiers in Physics, 2024)
The problematics of laser-induced fluorescence (LIF) measurements in a partially saturated regime with spatially dependent laser intensity in the sample (caused by absorption) is analysed. The obtained equations are tested by means of LIF of free tellurium atoms in a plasma of an atmospheric-pressure dielectric barrier discharge (DBD) by comparison of fluorescence and absorption measurements. The results show a high reliability of the LIF measurements.